Prevalence of Hypertension Among Pregnant Women When Using the 2017 American College of Cardiology/American Heart Association Blood Pressure Guidelines and Association With Maternal and Fetal Outcomes. Issue 8 (August 2021) - Bello, Natalie A.; Zhou, Hui; Cheetham, T. Craig; Miller, Eliza; Getahun, Darios; Fassett, Michael J.; Reynolds, Kristi
Abstract : (Abstracted from JAMA Netw Open 2021;4:e213808) Until 2017, the American College of Cardiology (ACC), American Heart Association (AHA), and American College of Obstetricians and Gynecologists (ACOG) had a common threshold for diagnosing hypertension: a blood pressure of 140/90 mm Hg or higher. That year, based on the outcomes of randomized trials on nonpregnant adults, the ACC-AHA lowered its recommended threshold to 130/80 mm Hg or higher.